Concurrent training reduces depressive symptoms in Mexican female older adults - Canton Martínez, Ermilo (2020)
Purpose: To determine the effect of a concurrent-training exercise program (CTEP) on mild depression in Mexican female OA. A secondary aim was to determine the correlation between physical function, body composition and depressive symptoms in OA following a CTEP. Methods: Twenty-one females (age= 64.0 ± 5.38 yr., weight= 72.0 ± 12.6 kg, BMI= 29.0 ± 4.7 kg/m2) participated in the study. Before (Pre) and after (Post) the CTEP, participants were measured on depression by the Hamilton Depression Rating Scale (HAM-D), body fat, muscle mass [MM]), physical function by the Senior Fitness Test, and aerobic capacity by the 6-min walking test (6MWT). The CTEP consisted in two days of aerobic exercise and one day of resistance training performed for 50-min at moderate intensity (12 to 14 on Borg’s RPE scale) for 12-weeks. Paired t-tests were computed to compare pre- to post-CTEP effects, and Spearman correlations studied the association between body composition, physical function and depression scores using the GraphPad PRISM 5.0 software. Results: The CTEP reduced HAM-D scores (Pre= 15.7 ± 4.5 vs. Post= 10.3 ± 5.3 pts., p=0.0001), improved upper-body strength (Pre= 15.1 ± 2.6 vs. Post= 18.9 ± 3.0 reps, p=0.0001), lower-body strength (Pre= 12.0 ± 2.4 vs. Post= 14.5 ± 2.9 reps, p= 0.0001), agility (Pre= 6.5 ±0.9 vs. Post= 6.0 ± 0.9 s, p=0.0001), and MM (Pre= 21.8 ± 2.9 vs. Post= 22.26 ± 3.1 kg, p=0.002). No significant changes were found in aerobic capacity (Pre= 587.9 ± 164.4 vs. Post= 619.6 ±144.9 m, p=0.06) and body fat (Pre= 31.0 ± 8.8 vs. Post= 30.8 ± 9.1%, p > 0.05). The HAM-D scores were inversely correlated with upper-body strength (r= -0.53, p=0.002) and lower-body strength (r= -0.64, p= 0.002), and directly correlated to agility (r= 0.50, p= 0.0004). Conclusions: A CTEP reduced depressive symptoms in Mexican female OA in spite of lack of changes in body composition. The increased physical function relates to a reduction in depressive symptoms; thus, highlighting the importance of improving functionality in OA.